Desain Pembelajaran Dick and Carey pada Materi Matematika Tingkat Lanjut Konsep Dasar Vektor Kelas XI SMA - Nita Adelyn; Tian Abdul Aziz (International Forum of Researchers and Lecturers, 2024)
Basic vector concept material will be more meaningful and able to hone students' mathematical communication skills if learning is implemented that is appropriate to the characteristics of students and needs in the field. The aim of this research is to create a research design for basic vector concept material using the Dick and Carey model. The results show that there are 10 steps that teachers need to pay attention to when creating learning designs and ensuring that the learning objectives contained are in accordance with learning achievements and needs in the field.